Pengaruh Independensi, Time Budget Pressure, Skeptisisme Profesional Auditor, Etika Auditor Dan Pengalaman Kerja Auditor Terhadap Kualitas Hasil Pemeriksaan Auditor Pemerintah Daerah (Survai Pada Inspektorat Kota/Kabupaten Se-Eks Karesidenan Surakarta) - Hapsari, Riana Eka (2016)
This research aims to know the influence of independence, time budget pressure, auditor's proffesional skepticism, auditor ethics and auditor's work experience toward the auditor's audit quality. The object of this research is Inspektorat office the residency of Surakarta. The sampling methodusedpurposive sampling (sample selection aims or in selecting the sample is not random).The number of respondents who participated in this research is 58 auditor and auditor staff. Techniquesandmethods ofdata analysisused inthis study usingmultiple linear regression analysiswith the help of SPSS 21program. The result of the research are independence and time budget pressure have no effect on the auditor's audit quality. While the variabeles; auditor's proffesional skepticism, auditor ethics and auditor's work experience have an effect on the auditor's audit quality. Keywords: independence, time budget pressure, auditor's proffesional skepticism, auditor ethics, auditor's work experience toward and auditor's audit quality.